MANEJO DA IRRIGAÇÃO E ADUBAÇÃO NITROGENADA NO FEIJOEIRO – CULTIVAR PÉROLA - MACIEL, Gustavo de França,; LOPES, Adriano da Silva,; FRANCO, Jhonatan da Silva,; Kraeski, Marcos Jefferson, (ANAIS DO ENIC, 2024)
-